Kompetensi Ustadzah Melalui Sertifikasi Untuk Meningkatkan Kualitas Pembelajaran di Taman Pendidikan Al-Quran Al-Aqsa - Romadoni, Fitri; Maesa Yunanda Tri Wijayanti; Serli Della Puspita; Salwa Airinnisa; Anisa Ika Febriyanti; Susilo, Heryanto; Tri Ulya Qodriyati (Program Studi Pendidikan Luar Sekolah, 2025)
Abstract: Quranic education plays an important role in shaping the character and morals of the young generation in Indonesia, especially in the Al-Aqsa Quranic Education Park (TPQ). However, the qualilty of learning in TPQ is often hampered by the less than optimal competence of the teaching staff. Therefore, improving the competence of teaching staff through training and certification is very important to ensure the quality of quality Quranic education.The research used to examine the improvement of the competence of female teachers at TPQ Al-Aqsa through certification to improve the quality of learning is descriptive qualitative. In qualitative studies, there are various methods for collecting data, such as observation, interviews, and documentation.This study aims to examine how training and certification programs can improve the competence of teaching staff and ultimately improve the quality off learning in TPQ AL-Aqsa. The result is that certification and training not only provide formal recognition, but also guarantee the quality of teaching of the Qur'an that is more effective and meets standards, producing students who understand the Qur'an better and have noble morals, while also answering the need for competent and professional teaching staff at TPQ Al-Aqsa. It is hoped that this study can contribute to improving the quality of islamic religious education in surabaya and its surroundings. Abstrak: Pendidikan Al-Quran memegang peranan penting dalam membentuk karakter dan akhlak generasi muda di Indonesia, khususnya di Taman Pendidikan Al-Quran (TPQ) Al-Aqsa. Namun, kualitas pembelajaraan di TPQ sering kali terkendala oleh kompetensi tenaga pendidik yang kurang optimal. Oleh karena itu, peningkatan kompetensi tenaga pendidik melalui diklat dan sertifikasi menjadi sangat penting untuk menjamin mutu pendidikan Al-Quran yang berkualitias. Penelitian yang digunakan untuk mengkaji peningkatan kompetensi ustadzah di TPQ Al-Aqsa melalui sertifikasi untuk meningkatkan kualitas pembelajaran adalah kualitatif deskriptif, Dalam studi kualitatif, terdapat berbagai metode untuk mengumpulkan data, seperti observasi, wawancara, dan dokumentasi Penelitian ini bertujuan untuk mengkaji bagaimana progam diklat dan sertifikasi dapat meningkatkan kompetensi tenaga pendidik dan pada akhirnya meningkatkan kualitas pembelajaran di TPQ Al-Aqsa. Hasilnya adalah sertifikasi dan diklat tidak hanya memberikan pengakuan formal, tetapi juga menjamin kualitas pengajaran Al-Qur’an yang lebih efektif dan sesuai standar, menghasilkan santri yang lebih memahami Al-Qur’an dan memiliki akhlak mulia, sekaligus menjawab kebutuhan akan tenaga pendidik yang kompeten dan profesional di TPQ Al-Aqsa Harapannya, penelitian ini dapat memberikan kontribusi bagi peningkatan kualitas pendidikan agama islamdi surabaya dan sekitarnya.